2023
DOI: 10.1021/acsenergylett.2c02893
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Impacts of Defect Sites in Metal–Organic Framework Catalysts under Varied Driving Forces

Abstract: Defects in metal–organic frameworks (MOFs) primarily manifest as missing linkers or metal nodes induced through synthesis, post-synthetic modification, and/or exposure to reaction conditions. By changing the nature of active site(s) and perturbing crystalline frameworks, defects confer physico­chemical alterations to MOF catalysts that may promote or inhibit intrinsic reactivity, electron transfer and excitation, and mass transport. However, the complexity and dynamic character of defects often obfuscate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This material exhibits an intermediate conversion profile under identical catalyst mass loading and initial reactant concentrations, but a higher Fe‐normalized pseudo‐first order rate constant of 16 ± 3 mol Fe −1 s −1 (Figure S13) than the rate constant for crystalline MIL‐101. Incomplete coordination with terephthalate ligands may lead to crystallization with lack of long‐range order and Fe sites that have higher reactivity; such defects can have varied effects on reactions and have demonstrated rate enhancement in some cases 54–57 . Indeed, water content (via TGA) is greater in this material than crystalline MIL‐101 (4.4 ± 0.4 vs. 2.4 ± 0.2 mmol/g, respectively), suggesting a higher defect density since water binds to hydroxyl moieties from missing metals or linkers and node sites missing a capping ligand 55 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This material exhibits an intermediate conversion profile under identical catalyst mass loading and initial reactant concentrations, but a higher Fe‐normalized pseudo‐first order rate constant of 16 ± 3 mol Fe −1 s −1 (Figure S13) than the rate constant for crystalline MIL‐101. Incomplete coordination with terephthalate ligands may lead to crystallization with lack of long‐range order and Fe sites that have higher reactivity; such defects can have varied effects on reactions and have demonstrated rate enhancement in some cases 54–57 . Indeed, water content (via TGA) is greater in this material than crystalline MIL‐101 (4.4 ± 0.4 vs. 2.4 ± 0.2 mmol/g, respectively), suggesting a higher defect density since water binds to hydroxyl moieties from missing metals or linkers and node sites missing a capping ligand 55 .…”
Section: Resultsmentioning
confidence: 96%
“…Incomplete coordination with terephthalate ligands may lead to crystallization with lack of long-range order and Fe sites that have higher reactivity; such defects can have varied effects on reactions and have demonstrated rate enhancement in some cases. [54][55][56][57] Indeed, water content (via TGA) is greater in this material than crystalline MIL-101 (4.4 ± 0.4 vs. 2.4 ± 0.2 mmol/g, respectively), suggesting a higher defect density since water binds to hydroxyl moieties from missing metals or linkers and node sites missing a capping ligand. 55 While more detailed structurefunctional analysis of this framework is out-of-scope for this text, here it is observed that the presence of less ordered networks promotes reactivity.…”
Section: Catalyst Characterizationmentioning
confidence: 86%
“…The structure of defects and thus their contribution to catalysis can also vary over the course of a reaction. Hence, computational and mechanistic studies guided by ex situ and operando/in situ ,,, characterization of defects, catalytic sites, and reaction intermediates are necessary to clarify the origin of catalytic activity and inform rational catalyst design.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of defects-and thus their contribution to catalysis-can also vary over the course of a reaction. Hence, computational and mechanistic studies guided by ex situ and operando/in situ 49,50,54,157 characterization of defects, catalytic sites, and reaction intermediates are necessary to clarify the origin of catalytic activity and inform rational catalyst design.…”
Section: Discussionmentioning
confidence: 99%